Efecto de la aplicación de abonos orgánicos en el cultivo de cafeto (Coffea Arabica l) en el distrito de Alonso de Alvarado Roque, provincia de Lamas - Pinedo Mori, Nery Antonio (2011)
In the San Martin region, growing coffee (Coffea arabica L.) has become very important. In the years 1996 - 1998, the recovery in prices in the international market, has determined the increase of new coffee areas, posesionando St. Martin in fourth in area and third in production volume 47 nationally with 768.00 ha. qq 548.00 and 612 respectively (MINAG -JNC, 2009). At present, the domestic and international market requires the production of organic cafes and very good quality. This market requirement could actually be accomplished, if farmers do the same in the culture of composting, this being a fundamental practice to achieve high yields. In St. Maarten, composting is not practiced, so that the farmers are paid not drastically impair their performance and eventually leave their plantations, thus causing more problems, since they have to deforesting areas to establish new plantations, practicing shifting cultivation. Using Microorganisms Mountain (MM) as accelerators in the breakdown for the production of organic fertilizers on coffee farms, is to give an alternative to the lack of culture of composting, this at a relatively low cost, since inputs with which it is told in the farms and often wasted by not giving proper use is used. This research was performed under the Specialty Coffee Project, implemented by the NGO Capirona, which are comparatively evaluated the effect of the application of three sources of organic fertilizers such as compost classic, compost microorganisms Mountain (MM ) and recommended standard Sanchez manure Escalante, in order to see the effect on crop yield and the nutrient enrichment of the soil to enable their recovery. Thus, it is intended to help the farmers to use organic fertilizers that are most appropriate and effective to increase production and quality of coffee.